Effectiveness of Clinical Decision Support Systems on the Appropriate Use of Imaging for Central Nervous System Injuries: A Systematic Review - Zare, Sahar; Mobarak, Zohre; Meidani, Zahra; Nabovati, Ehsan; Nazemi, Zahra (Applied Clinical Informatics, 2022)
Background One of the best practices for timely and efficient diagnoses of central nervous system (CNS) trauma and complex diseases is imaging. However, rates of imaging for CNS are high and impose a lot of costs to health care facilities in addition to exposing patients with negative impact of ionizing radiation.Objectives This study aimed to systematically review the effects and features of clinical decision support systems (CDSSs) for the appropriate use of imaging for CNS injuries.Method We searched MEDLINE, SCOPUS, Web of Science, and Cochrane without time period restriction. We included experimental and quasiexperimental studies that assessed the effectiveness of CDSSs designed for the appropriate use of imaging for CNS injuries in any clinical setting, including primary, emergency, and specialist care. The outcomes were categorized based on imaging-related, physician-related, and patient-related groups.Result A total of 3,223 records were identified through the online literature search. Of the 55 potential papers for the full-text review, 11 eligible studies were included. Reduction of CNS imaging proportion varied from 2.6 to 40% among the included studies. Physician-related outcomes, including guideline adherence, diagnostic yield, and knowledge, were reported in five studies, and all demonstrated positive impact of CDSSs. Four studies had addressed patient-related outcomes, including missed or delayed diagnosis, as well as length of stay. These studies reported a very low rate of missed diagnosis due to the cancellation of computed tomography (CT) examine according to the CDSS recommendations.Conclusion This systematic review reports that CDSSs decrease the utilization of CNS CT scan, while increasing physicians' adherence to the rules. However, the possible harm of CDSSs to patients was not well addressed by the included studies and needs additional investigation. The actual effect of CDSSs on appropriate imaging would be realized when the saved cost of examinations is compared with the cost of missed diagnosis.
Keywords: clinical decision support system; computer-assisted decision-making; appropriateness reviews; hospitals; radiology; imaging; central nervous system; evaluation of impact